Procedimientos lingüísticos en la obra literaria de Alonso Zamora Vicente - Sánchez Lobato, Jesús (Revista de Filología Románica, 2008)
This article is the result of the analysis of some different works by Alonso Zamora Vicente. Our purpose is to study the main linguistic proceadures used as literary resources.